2004
DOI: 10.1130/g20548.1
|View full text |Cite
|
Sign up to set email alerts
|

Igneous dikes on Mars revealed by Mars Orbiter Laser Altimeter topography

Abstract: The origin of Martian grabens has remained controversial for decades, given the nonuniqueness of graben morphology and conflicting interpretations of dike-induced or faultingbased formation processes. We use measurements from the Mars Orbiter Laser Altimeter to identify the characteristic topographic signature at the surface of an igneous dike beneath a Martian graben. Our results suggest that this subtle but diagnostic signature can be used to test competing interpretations of the formation of grabens and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 29 publications
4
49
1
Order By: Relevance
“…Venusian graben along fracture zones may be linked to mantle dynamics (Solomon et al, 1991) or gravitational spreading (Phillips and Hansen, 1994), while graben observed around coronae and chasmata are likely due to loadinduced stresses (upwelling or loading of magmatic material) or as dilation over dike intrusions (Hansen and Phillips, 1993;Ernst et al, 2003;Krassilnikov and Head, 2003;Grindrod et al, 2005). Martian graben are thought to originate either as a consequence of tectonic rifting, dilation over dike intrusions, or from loadinduced stresses (i.e., Tharsis) (Banerdt et al, 1992;Wilson and Head, 2002;Cailleau et al, 2003;Mège et al, 2003;Schultz et al, 2004;Golombek and Phillips, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Venusian graben along fracture zones may be linked to mantle dynamics (Solomon et al, 1991) or gravitational spreading (Phillips and Hansen, 1994), while graben observed around coronae and chasmata are likely due to loadinduced stresses (upwelling or loading of magmatic material) or as dilation over dike intrusions (Hansen and Phillips, 1993;Ernst et al, 2003;Krassilnikov and Head, 2003;Grindrod et al, 2005). Martian graben are thought to originate either as a consequence of tectonic rifting, dilation over dike intrusions, or from loadinduced stresses (i.e., Tharsis) (Banerdt et al, 1992;Wilson and Head, 2002;Cailleau et al, 2003;Mège et al, 2003;Schultz et al, 2004;Golombek and Phillips, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these tectonic complexes exhibit distinct sets of graben that extend radially for distances of hundreds to thousands of kilometres (Carr 1974;Plescia & Saunders 1982;Scott & Tanaka 1986;Tanaka et al 1991;Mège & Masson 1996;Anderson et al 2001). Formation of these graben has been attributed to crustal extension (Plescia & Saunders 1982;Banerdt et al 1992;Phillips et al 2001) and/or dyke propagation (Mège & Masson 1996;Scott et al 2002;Schultz et al 2004).…”
mentioning
confidence: 99%
“…LOLA topographic data will be used to discriminate between magmatic and non-magmatic tectonism, and to constrain the volumes of the underlying magma bodies. Similar analyses have been successfully applied to the study of dikes on the Earth and Mars (e.g., Schultz et al 2004).…”
Section: Fig 4 (Continued)mentioning
confidence: 94%